Implications of modelled radioactivity measurements along coastal Odisha, Eastern India for heavy mineral resources. (5th January 2017) - Ghosal, S.; Agrahari, S.; Guin, R.; Sengupta, D.
Abstract: A radioelemental assemblage assessment of two beaches of Odisha is performed for the first time. The radiation is measured in two ways, both on field with the help of a hand held environmental survey meter and in the laboratory, where the concentrations of radionuclide's 238 U, 232 Th and 4 K have been determined with the help of High Purity Germanium detector (HPGe). Mineralogical analysis of selected samples has been performed with the help of X-Ray Fluorescence Spectrometry (XRF). A marked difference between the concentration of Uranium (274 Bq kg −1 ) and Thorium (2489 Bq kg −1 ) is observed and discussed based on the geology of the area. The placer deposits showing an enrichment of thorium can be an important source of nuclear fuel for the thorium based nuclear reactors. The ratio of thorium and uranium concentrations gives us an idea about the coastal processes associated with the beach. Statistical analysis of the data shows a positive correlation between 238 U and 232 Th and a strong negative correlation is indicated between 4 K and 238 U, 232 Th. A cross plot between the equivalent thorium and the equivalent uranium and the equivalent thorium and potassium, represents the nature of deposition and its association with the heavy mineral along with the radioactive elements. Heavy minerals exhibit an increasing trend towards Northeast-Southwest along the south eastern coast of India. Graphical abstract: Highlights: Assessment of radio elemental concentration of sand samples from Odisha by HPGe. Th/U ratio indicates monazite enrichment by a factor of 1.3. High heavy mineral assemblage in the area is inferred from a cross plot. Enrichments of heavy minerals are following a NE-SW trend.